On the stratigraphic position of kaolin in Väyrylänkylä, South Puolanka area, Finland - K. Laajoki (Bulletin of the Geological Society of Finland, 1975)
Drilling data on the stratigraphic position of recently discovered clay occurrences containing kaolinite are given. Preliminary information on the clay minerals involved is included. The weathering undergone by the Precambrian rocks underlying the clays is described briefly. Secondary enrichment of iron caused by weathering in iron formations as revealed by partial ore analyses is presented. The clays lie between strongly folded Karelidic rocks and Quaternary deposits, and are thus Preglacial in age. Owing to the varying kaolinite content (0–60 %) and the thick Quaternary overburden the clays are not economically exploitable. The kaolin of Pihlajavaara, which some authors have considered to be of Karelian age, is correlated by the present author with Preglacial clays.